Analisis Spasial Distribusi SSS Menggunakan Data Citra Landsat 8-OLI Sebagai Pedoman Dalam Mitigasi Korosi Laut (Studi Kasus: Perairan Teluk Kendari) - Nurgiantoro, Nurgiantoro; Hamdhana, Hamdhana (Masyarakat Ahli Penginderaan Jauh Indonesia (MAPIN) /Indonesian Society of Remote Sensing (ISRS), 2019)
Spatial Analysis of SSS Distribution Using 8-OLI Landsat Imagery As a Guide In Mitigating of Marine Corrosion (Case Study: Kendari Bay Waters) Sea surface salinity (SSS) is the amount of dissolved salt in sea water expressed in psu. Besides being able to be measured directly on the field, SSS could also be extracted from satellite image data. This study objective is to explain how SSS is extracted from Landsat 8 data to determine the distribution of SSS in Kendari Bay waters. Furthermore, distribution and patterns are used as guidelines for mitigating corrosion due to seawater on coastal building materials. In this study, SSS was extracted using channel-ratios with wavelengths of 450-510 nm and 530-590 nm, for 5 years (2014-2018). The results show that in 2014-2018 the estimated-SSS was 8,583 psu, 8,612 psu, 8,627 psu, 8,273 psu, and 8,372 psu; respectively. In the open sea, the salinity range is generally in the range of 33-37 psu with elative constant value. River runoff and high rainfall are the main factors in low SSS waters in Kendari Bay.